The effect of esketamine on emergence delirium in pediatric patients undergoing general anesthesia: a meta-analysis of randomized controlled trials - Li, Shiyue; Li, Yue; Gao, Pengfei (Frontiers in Pharmacology, 2025)
BackgroundThe aim of this study was to investigate the effect of esketamine on emergence delirium in pediatric patients.MethodsWe searched Pubmed, Cochrane Controlled Register of Trials, and Embase from inception to December 2024. Studies were independently evaluated for inclusion criteria and exclusion criteria by two reviewers. The primary outcome was the incidence of emergence delirium during the post-anesthesia period. The secondary outcomes were the PAED scores, FLACC scores, PACU stay time, and the incidence of nausea and vomiting.ResultsTen studies including 853 children were eligible for this meta-analysis. The pooled data revealed that esketamine administration significantly reduced the incidence of emergence delirium in pediatric patients (RR: 0.40, 95% CI: 0.30–0.53, P < 0.00001, I2 = 4%). Compared with the control group, esketamine also displayed lower PAED scores (MD: -3.66, 95% CI: -5.85–1.47, P = 0.001, I2 = 99%) and FLACC scores (MD: -2.47, 95% CI: -3.32–1.61, P < 0.0001, I2 = 89%). Esketamine had no significant effect on the PACU stay time (MD: 0.5 min, 95% CI: -1.51–2.51, P = 0.63, I2 = 61%) and the incidence of nausea and vomiting (RR: 0.7, 95% CI: 0.46–1.06, P = 0.09, I2 = 0%).ConclusionThe administration of esketamine can reduce the incidence of emergence delirium without prolonging PACU stay time and increasing the risk of nausea and vomiting in pediatric patients. Subgroup analysis indicated that a single bolus esketamine before anesthesia induction or at the end of surgery would better reduce the risk of ED than intraoperative continuous infusion.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024623667.